Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di TK Islam Terpadu Izzatul Islam Karawang - Risma Septiani; Syamsudin Syamsudin (Thawalib: Jurnal Kependidikan Islam, 2022)
The purpose of this study was to determine the role of the principal in improving teacher performance in Izzatul Islam Integrated Islamic Kindergarten, Cengkong Village, Purwasari District, Karawang. The research method is qualitative, namely by describing, revealing, explaining, and analyzing phenomena, events and activities that occur at the research location. Data collection techniques are interviews, observation and documentation. The results showed: the principal as a leader, namely directing teachers to carry out their duties and responsibilities. As educators, by conducting direct coaching (supervision) or coaching outside of school. As administrators and motivators, principals teach teachers to collaborate in creating and compiling school programs. The principal manages and empowers all human resources to optimize their abilities. As innovators, principals provide opportunities for teachers to be creative and innovate in schools. The results of the coaching and training carried out by principals for teachers can increase their performance abilities by 85%.